The Effect of the Teaching Strategy According to the Cognitive Path Model on the Skill of Processing Mathematical Information among First Middle School Students (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify the effect of a teaching strategy according to the knowledge path model on the skill of processing mathematical information among first-intermediate students in mathematics. The researchers adopted an experimental research approach and a quasi-experimental design. The experiment was applied to a sample of 65 first intermediate students: 33 students were assigned to the experimental group and 32 students were assigned to the control group for the academic year (2022-2023). The researcher designed a test of 18 essay-type items to measure the skill of processing mathematical information. The results showed that the students of the experimental group who were taught according to the proposed strategy outperformed the students of the control group who were taught according to the traditional method in the mathematical information processing test. In light of the results, the research came out with a set of recommendations and suggestions.